Penerapan Model Project Based Learning Dalam Pembelajaran IPA Untuk Meningkatkan Hasil Belajar Dan Membangun Karakter Abad 21 Siswa Kelas IV - Hartati Hartati (Pedir Research Institute, 2022)
This thesis begins from preliminary observations at MIN I Kulon Progo, data obtained that learning with project-based learning model is still not maximally used so learning is less optimal especially in science education. This thesis discusses about class with project-based learning model toward learning outcomes and building 21st century character for 4th grade students of MIN I Kulon Progo, with the topic of discussion in science education in 2017/2018 is force. This study aims to: (1) What are the learning outcomes of 4th grade students of MIN I Kulon Progo with Project-Based Learning in science education?, (2) How Project-Based Learning method influence 4th grade students of MIN I Kulon Progo in improving learning outcomes?, (3) Are there differences in learning outcomes of students with Project-Based Learning model?, (4) How is the application of Project-based learning model in building 21st century character to the students.?. This research uses mixed research method with transformative approach, method of collecting the data uses several techniques which are observation, tests, interviews and documentation. For method of analyzing the data gained from quantitative and qualitative data. The results of this study indicate that: (1) The results of the class average score of experimental class (project based learning model) are higher than the control class (5M model), namely the experimental class (Project-Based Learning Model) is 82.75, while the control class (5M Model) is 75.50. (2) Project-Based Learning model influences the improvement of student learning outcomes with a mean difference of 7.25. (3) There is no difference in learning outcomes of 4th grade students of MIN I Kulon Progo with Project-Based Learning method based on the score calculation of Post-Test, the t-value <t-table (1.598 <2.0244) and p value 0.05 (0.118> 0.05) then Ho is accepted and ha is rejected. (4) Project-based learning model can build students' 21st century character.